PENGARUH KUALITAS SISTEM INFORMASI MANAJEMEN, LINGKUNGAN KERJA, DAN DESENTRALISASI TERHADAP KINERJA KARYAWAN DI PD. BKK CABANG KARANGANYAR - Mulyono & Rohwiyati (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This study aims to determine the effect quality of management information system, work environment and decentralization on employee performance in PD BKK Branch Karanganyar. Hypothesis in this study is quality of management information system, work environment and decentralization have a significant effect on employee performance in PD BKK Branch Karanganyar. This study using sample of 153 respondents. Data analysis technique using multiple linear regression. The results of this study that quality of management information system, work environment and decentralization have a significant effect on employee performance in PD BKK Branch Karanganyar.Keywords: quality of management information system, work environment, decentralization, performance.